Recovery of spent LiCoO2 lithium-ion battery via environmentally friendly pyrolysis and hydrometallurgical leaching - Tao, Ren; Xing, Peng; Li, Huiquan; Sun, Zhenhua; Wu, Yufeng (Resources, conservation and recycling, 2022)
LiCoO2 (LCO) lithium-ion battery (LIB) is rich in valuable metals (cobalt and lithium), which has high recycling value. The existing process has basically realized the extraction of cobalt, but there are still shortcomings in harmless disposal of fluorine-containing electrolyte, binder and other organic matters, selective extraction of lithium and low-cost extraction of cobalt. In this context, a novel process was developed to realize the full-component recovery of spent LiCoO2 battery via environmentally friendly pyrolysis and hydrometallurgical leaching. The organic matters were recovered in the form of pyrolytic oil and gas, in which the harmful fluorine element was absorbed by Ca(OH)2 solution. The current collectors (copper and aluminum) were recovered after the easy separation of electrode materials due to the degradation of binders. During pyrolysis the cathode material was deconstructed and reduced under the synergistic effect of pyrolytic gas and anode graphite. Selective recovery of lithium and cobalt was achieved through carbonated water leaching and reductant-free acid leaching. The leaching efficiencies of lithium and cobalt were respectively 87.9% and 99.1% under the optimal conditions. Lithium carbonate and cobalt sulfate were obtained by evaporative crystallization, respectively. The remaining residue was only graphite without impurity entrainment. The results in this research suggest that the process consisting of pyrolysis and hydrometallurgical leaching is inexpensive, efficient, and eco-friendly for full-component recycling of spent LiCoO2 battery. [Display omitted]